نظام الحكم في السودان - د. محمد نصر عبد الله (White Nile Journal for Studies and Research, 2023)
This research which entitled the system of governance in the Sudan. Aims at clarifying the suitable system of ruling the Sudan. The reason for choosing this topic of research is that the system of governing is considered one of the current issues that worth studying and clarifying. The problem of the research is represented in the way of choosing the suitable system of ruling of the Sudan. The researcher chooses the historical approach. The nature of the research compels to be divided into three different chapters. The first chapter is entitled the "the concept of governance", the second chapter is entitled "the system of ruling in the Sudan and explaining the best one" and the third one is entitled "the role of inspection of the high court in the continuity of the system of ruling the Sudan". The conclusion reflects the most important results and the recommendations. Some of the results are: the method of choosing a suitable system of governing in the Sudan helps in solving a number of problems which face the society and the governments. The most important recommendations are: the choosing and applying of democracy in making the suitable system of ruling in the Sudan. In conclusion with the research. is attached the references page